2015
DOI: 10.1186/s13617-015-0037-7
|View full text |Cite|
|
Sign up to set email alerts
|

Fearing the knock on the door: critical security studies insights into limited cooperation with disaster management regimes

Abstract: In seeking to provide for the safety of local communities in the global south, there has been an apparent policy focus on making early warning systems more robust, and improving the operation of disaster management programmes. However, the critical security studies literature has highlighted the ways in which security practices, including those nominally implemented on behalf of local communities can have negative impacts on peoples. Human security literature, in particular, highlights the ways in which the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 74 publications
0
20
0
1
Order By: Relevance
“…Cotopaxi hazard maps have been published in several versions since 1976, with the newest version published in late 2016 (Mothes et al 2016a). The IGEPN has carried out a long-term program of community education for areas that are at highest risk, although as noted by Christie et al (2015), the attention over such a vast area (%2000 km 2 ), was uneven. Cotopaxi was a VUELCO target volcano from 2013 to 2015.…”
Section: Monitoring Cotopaximentioning
confidence: 99%
See 1 more Smart Citation
“…Cotopaxi hazard maps have been published in several versions since 1976, with the newest version published in late 2016 (Mothes et al 2016a). The IGEPN has carried out a long-term program of community education for areas that are at highest risk, although as noted by Christie et al (2015), the attention over such a vast area (%2000 km 2 ), was uneven. Cotopaxi was a VUELCO target volcano from 2013 to 2015.…”
Section: Monitoring Cotopaximentioning
confidence: 99%
“…Work by Christie et al (2015) (an earlier VUELCO contribution) had shown that residents of the Chillos valley, to the east of Quito, were particularly ill-prepared to confront lahar hazards due to their recency of living in that valley. On the other hand, residents of the Latacunga valley had a clearer memory of lahar hazards, since many of their distant relatives had lived through Cotopaxi eruptions and their collective memory is better preserved.…”
Section: The Science-society Interfacementioning
confidence: 99%
“…Furthermore, the stakes for at-risk communities are high, given that communications of scientific knowledge, when poorly handled, can cause social, economic and political problems, even if the identified hazards do not lead imminently to physical consequences such as an eruption (Johnston et al 2002). There is thus a constant risk that community confidence in disaster management regimes could be undermined (Christie et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Christie et al 2015), and encourage citizens at risk to act on advice. In particular more systematic studies that analyse the effectiveness of different techniques and strategies in achieving these goals would be very useful (see Fearnley et al 2017 for a recent compilation).…”
Section: (B) Improved Communicationmentioning
confidence: 99%
“…Uncertainties in the decision-making process may give rise to "false alerts" (i.e., false positives; see Table 2) and actions by civil protection with adverse impacts on the compliance of affected communities in future unrest events. (3) Lack of globally accepted and standardised approach for the terminology, methodology, (Johnson 1987;Haynes et al 2008;Christie et al 2015;Komorowski et al 2017). …”
Section: The Caveats Of Volcanic Unrest Responsementioning
confidence: 99%